Mechanical properties and cytotoxicity of a resorbable bioactive implant prepared by rapid prototyping technique. Issue 10 (18th March 2013) - El‐Ghannam, Ahmed; Hart, Amanda; White, Dean; Cunningham, Larry
<x xml:space="preserve">Abstract</x> Bioceramic processing using rapid prototyping technique (RPT) results in a fragile device that requires thermal treatment to improve the mechanical properties. This investigation evaluates the effect of thermal treatment on the mechanical, porosity, and bioactivity properties as well as the cytotoxicity of a porous silica‐calcium phosphate nanocomposite (SCPC) implant prepared by RPT. Porous SCPC implant was subject to 3‐h treatment at 800°C, 850°C, or 900°C. The compressive strength (s) and modulus of elasticity (E) were doubled when the sintering temperature is raised from 850 to 900°C measuring (s = 15.326 ± 2.95 MPa and E = 1095 ± 164 MPa) after the later treatment. The significant increase in mechanical properties takes place with minimal changes in the surface area and the percentage of pores in the range 1–356 μm. The SCPC implant prepared at 900°C was loaded with rh‐BMP‐2 and grafted into a segmental defect in the rabbit ulna. Histology analyses showed highly vascularized bone formation inside the defect. Histopathological analyses of the liver, spleen, kidney, heart, and the lung of rabbits grafted with and without SCPC demonstrated healthy tissues with no signs of toxicity or morphology alterations. Results of the study suggest that it is possible to engineering the mechanical properties of the SCPC implant without compromising its bioactivity. The enhanced bone formation inside the porous SCPC facilitated cell‐mediated graft resorption and prohibited any accumulation of the material in the body organs. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 2851‐2861, 2013.